2020
DOI: 10.3389/fmicb.2019.03069
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Moderately Thermophilic Solvent-Tolerant Esterase Isolated From a Compost Metagenome Library

Abstract: A novel esterase, EstCS1, was isolated from a compost metagenomics library. The EstCS1 protein, which consists of 309 amino acid residues with an anticipated molecular mass of 34 kDa, showed high amino acid sequence identities to predicted esterases and alpha/beta hydrolases (59%) from some cultured bacteria and to predicted lipases/esterases from uncultured bacteria. The phylogenetic analysis suggested that the EstCS1 belongs to the hormone-sensitive lipase family of lipolytic enzyme classification and contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…In comparison with family IV esterases from similar compost metagenomic sources, Est8L had poor organic solvents stabilities, whereas EstCs1 from a compost metagenomic library was stable at 30% isopropanol, ethanol, acetonitrile, acetone, methanol, dimethyl formamide, and dimethyl sulfoxide [10]. In addition, Est8L was optimally active at pH 10.0, whereas EstCs1 was optimally active at pH 8.0 [10]. In enantioselectivity, Est8L hydrolyzed the S-form with 10.1% higher activity than the R-form, suggesting preferences for the S-form, whereas Est13L showed no selectivity for the enantiomers (Figure 12).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In comparison with family IV esterases from similar compost metagenomic sources, Est8L had poor organic solvents stabilities, whereas EstCs1 from a compost metagenomic library was stable at 30% isopropanol, ethanol, acetonitrile, acetone, methanol, dimethyl formamide, and dimethyl sulfoxide [10]. In addition, Est8L was optimally active at pH 10.0, whereas EstCs1 was optimally active at pH 8.0 [10]. In enantioselectivity, Est8L hydrolyzed the S-form with 10.1% higher activity than the R-form, suggesting preferences for the S-form, whereas Est13L showed no selectivity for the enantiomers (Figure 12).…”
Section: Discussionmentioning
confidence: 97%
“…Family IV and VIII esterases have been practically interested in the usage of ester synthesis, transesterification reactions, and hydrolysis of antibiotics [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of industrial bioconversion catalyzed by lipolytic enzymes are usually conducted in non-aqueous medium (Oh et al 2012), researchers are dedicated to search for solvent-tolerant enzymes (Zarafeta et al 2016;Park et al 2020) or adopt directed evolutionary approach to acquire stable enzymes in hydrophilic organic solvents (Hyun et al 2012). EstQ7 showed moderate tolerance to a range of organic solvents (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Metagenomic strategy provides an access to genomes of the uncultured microorganisms skipping culturing microorganisms and have been applied to screen novel biocatalysts for industrial applications in the past decades (Handelsman 2004). Various novel biocatalysts have been successfully identi ed from soil metagenomic library, such as lipolytic enzymes (Li et al 2018;Park et al 2020), proteases (Gong et al 2017), cellulases (Garg et al 2016;Yang et al 2016), and novel natural products (Katz et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It can catalyze the breaking of ester bonds to form the corresponding alcohols and acids with water molecules [10]. Esterases are distributed in plants, animals, and microorganisms, and among them the microbial esterases are found to be more stable and favourable for production at a large scale [11][12][13][14][15]. Esterase is also used to resolve (R, S)-DMPM.A study reported that the enantiomeric excess of lipase MC 16-3 and lipase 99-2-1 resolution (R, S) -DMPM from Burkholderia sp.were 91.8% (conversion rate 25%) and 91%(conversion rate 30%).…”
Section: Introduction (R)-mentioning
confidence: 99%